السجع في سورة الرحمن: دراسة تحليلية بلاغية: The Rhyme Prose in the verse of “Rahman: Rhetorical analytical study - Mohd Nawi, Muhammad Zulazizi (SIBAWAYH Arabic Language and Education, 2022)
اعتمد هذا البحث على السجع في سورة الرحمن. والسجع هو أحد فروع من المحسنات اللفظية حول محور مناقشة علم البلاغة في علم البديع. هذا البحث يقدم الفهم والتبيان إلى من لم يفهموا عن السجع بشكل موضوعي. أنّ هذا البحث يقدم المنهج المكتبي والتحليلي، يعني الباحث يحتاج الرجوع إلى المصادر من الكتب البلاغة الذين يتعلق بالسجع. ويدرس هذا البحث عن السجع وجماله في علم البلاغة. سيقوم الباحث بالتعرف معنى السجع والإستفادة من الأمثلة عنه حتى توضيح صورة السجع ومفهومه. ثم، تحليل الباحث عن السجع في سورة الرحمن لتبحث عن عدد السجع في سورة الرحمن والتعرف موقعة أساليب السجع في سورة الرحمن. ونتيجة من هذا البحث، أورد الباحث أنّ سورة الرحمن تتضمن فيها أساليب بلاغية لا سيما بما تتعلق بالسجع.This research is discussing “As-Saja’” (Rhymed Prose) in the verse of “Rahman”. “As-Saja’” is one of the various forms of “Muhasanat Lafziah” (Beautiful of Verbal) discussion in the vicinity of “Balaghah” (Rhetoric). This research gives an understanding and explanation for those who didn’t understand “As-Saja’”. And this research focuses on analysis research based on a qualitative method which means the researcher refers to sources from books “Balaghah” that relate to “As-Saja’”. This research studies “As-Saja’” and its specialty in “Ilmu Balaghah” (Rhetorical Knowledge). The researcher will start this research with the elaborate meaning of “As-Saja’” and gives examples until understands it. Then, the researcher will search ‘Uslub As-Saja’” (Rhymed Prose Style) in the verse of “Rahman” to identify the number and position of “Uslub As-Saja’” in this verse. The resulting research shows that the verse of “Rahman” contains with ‘Uslub Balaghah’ (Rhetorical Style) includes the “As-Saja’”.Keywords: Rhymed Prose, Beautiful of Verbal, the verse of “Rahman”, Rhetorical Knowledge, Rhymed Prose Style